Dispersal of bryophytes and ferns is facilitated by small mammals in the boreal forest. Issue 3 (1st October 2016) - Barbé, Marion; Chavel, Émilie E.; Fenton, Nicole J.; Imbeau, Louis; Mazerolle, Marc J.; Drapeau, Pierre; Bergeron, Yves
ABSTRACT: Bryophytes and pteridophytes are important contributors to ecosystem services in boreal regions. Abiotic agents are considered their main dispersers, but recent studies suggest that biotic agents including invertebrates, birds and large mammals might also be efficient dispersal agents. Dispersal of cryptogams by ground-dwelling small mammals is often assumed to occur, but has yet to be demonstrated. In this study, we present the first evidence of boreal cryptogam species being dispersed by ground-dwelling small mammals. In 2013 and 2014, we recorded bryophyte cover and fern presence in 35 sites in black spruce forest. We also collected diaspores by brushing the fur of 99 ground-dwelling small mammals live-trapped in the same sites. Diaspores were then germinated on nutrient agar for six months. Viable diaspores of five bryophyte species and one fern species were successfully grown. No association was found between the cryptogam community sampled on site and the diaspore community grown on artificial substrate. Unlike abiotic agents that randomly disperse cryptogams, small mammals are more likely to transport diaspores to suitable substrates where microhabitat requirements for germination are met. Our results highlight the need to consider a broad spectrum of dispersal agents when focusing on the community dynamics of cryptogams.